Kinerja Pustakawan Layanan Sirkulasi Dalam Memanfaatkan Senayan Library Management System (SLiMS) - Ridwan, Parid; Sudarsana, Undang; Ruqoyah, Farah (Media Nusantara, 2021)
This study aims to determine the knowledge, skills, attitudes, and obstacles faced by librarians in utilizing SLiMS in the UPT Library of Pasundan University Bandung. The method used in this research is the descriptive method with a qualitative approach, while the data interview technique is through observation, interviews, and documentation study. From the research results, it can be concluded that the knowledge and understanding of circulation service librarians in utilizing the circulation service module SLiMS can be said to be good because SLiMS can help work without any difficulties in learning and operating it. The skills of service librarians who are served in utilizing SLiMS features can be said to be skilled. The attitude of librarian services in utilizing Slims circulation can be said to be good. SLiMS is able to cut the time needed to do a job. The obstacles experienced by circulation service librarians are in installing SLiMS and adding features according to the needs of circulation services, such as independent extension and sms gateway menu where the menu serves as a reminder for library users if they experience delays in returning books, and librarians do not have basic programming because SLiMS in its manufacture uses the PHP programming language.